Kearifan Lokal Penataan Ruang Wilayah Mukim Yang Berkelanjutan Di Aceh - T Nazaruddin; Sulaiman; Yulia (Arena Hukum, 2022)
Until now there has not been an in-depth and comprehensive of spatial planning based on local wisdom as strengthening the specificity of the Aceh region based on Law Number 11 Year 2016 concerning Aceh Government and Qanun No. 4 of 2003 concerning the Mukim Government. The purpose of this study is to analyze the local wisdom of spatial planning for sustainable settlements in Aceh. This research is a normative-supported empirical law study. The results showed that in the preparation of the Rencana Tata Ruang Wilayah (RTRW) the Mukim/mukim was not involved. In fact, information regarding the RTRW documents was never shared with the Imeum Mukim. The results of research in the residential areas of Aceh Besar, Pidie Jaya and North Aceh districts found that generally Mukims submitted the same complaints where Mukim was not informed or involved in the preparation of the RTRW in their area. Mukim’s authority is only limited to the resolution of disputes arising among the residents of the village in the Mukim region.